Nondilutive CoCo Bonds: A Necessary Evil? - Gamba, Andrea; Gong, Joe Yanxiong; Ma, Kebin (The Review of Corporate Finance Studies, 2025)
Abstract Banks predominantly issue nondilutive CoCos, contrary to the suggestion that CoCos should be dilutive to reduce risk-taking. In an agency model of two moral hazards, we show that, although dilutive CoCos deter ex ante risk-taking and prevent banks from being undercapitalized, penalizing shareholders of a distressed bank with dilution leads to ex post risk-shifting. CoCos’ design and risk implications depend on bank capitalization: equity-constrained banks prefer nondilutive CoCos because they maximize the financing capacity by tackling ex post risk shifting only. Nondilutive CoCos can be used to implement the constrained social optimum for highly leveraged banks, and regulators can induce appropriate CoCo designs with capital regulations. (JEL G21, G28)